Determining the benefits realization management practices and processes in clinical trials - Nonyane, Molati (Department of Construction Economics and Management, 2020)
Benefits are measurable improvements that result from project outcomes. There is an emphasis in clinical trials literature that clinical trial benefits must always outweigh the risks yet there is limited clarity on processes to manage and ensure delivery of those benefits. With uncertainty around the delivery of clinical trial benefits, it is worth adopting a balanced management approach. This study looked to establish whether there were any comprehensive benefits management processes in HIV clinical trials and compared these practices to those described in the literature. Methods: To assess the current benefits management practices used to manage HIV clinical trials, a cross-sectional study used a critical review of clinical trials guidelines and publications as well as an online survey that was distributed to stakeholders in clinical trials management. Results: The critical review of the guidelines and literature revealed a high emphasis on risk benefit assessment, but very limited mention of the processes used for the assessment and management of those risks and benefits. The diverse group of clinical trials managers that responded to the online survey were involved at the strategic level of their respective clinical trials and 74% of them had never heard of Benefits Realization Management (BRM) and BRM processes. The respondents however, acknowledged that their lack of awareness did not necessarily mean lack of existence of BRM or BRM processes in HIV clinical trials. There were aspects of benefits management practices in clinical trials that were found to be similar to those in literature and other industries such as benefits planning, benefits identification, benefits review, setting time scale to benefits realization and allocating benefits champions. Even though there was confidence from the respondents in how clinical trial benefits were managed and in clinical trials delivering their promise, the respondents still believed there was room for improvement in the current BRM processes. Conclusion: BRM processes are not readily visible or documented in HIV clinical trials. There is a management bias towards safety and ethics in clinical trials which seems to have resulted in limited focus on benefits management. Compared to other industries, there appears to be more room and opportunity to implement published BRM processes. The findings from this study will serve as a starting point for future studies on how BRM can be incorporated into current management practices in order to achieve the most out of clinical trials.